The relationship between psychopathology, psychosocial adjustment, social support and quality of life in multiple sclerosis - Kotan, Vahap Ozan; Kotan, Zeynep; Aydın, Birgül; Taşkapılıoğlu, Özlem; Alkan, Berna; Özkaya, Güven; Sarandöl, Aslı; Turan, Ömer Faruk; Kırlı, Selçuk (The European Research Journal, 2019)
Objectives: Multiple Sclerosis (MS) is a chronic disease which affects physical,psychological and social functioning of patients. In this study we aim to indicate psychiatric comorbidity, some psychosocial factors and their associations with quality of life in patients with MS. Methods: A total of 227 patients underwent psychiatric examination and the following scales were applied: Socio-demographic data form, Hospital Anxiety and Depression Scale (HADS), Multiple Sclerosis Quality of Life-54 (MSQOL-54), Psychosocial Adjustment to Illness Scale-Self report (PAIS-SR) and Multidimensional Scale of Perceived Social Support (MSPSS). Results: Among 227 patients with MS, 67.8% (n = 154) had psychiatric diagnosis; 24.2% (n = 55) had depression,19.8% (n = 45) had adjustment disorder, 14.9% (n = 34) had anxiety disorder, 7.1% (n=16) had dysthymic disorder and 1.8% (n = 4) had bipolar disorder. Patients with a psychiatric diagnosis had lower scores in role limitations due to emotional problems, emotional well-being, health perceptions, social function, cognitive function, health distress and mental health composite of MSQOL-54. PAIS-SR and MSPSS scores were significantly lower in MS patients with a psychiatric diagnosis. PAIS-SR scores were negatively correlated with role limitations-emotional, emotional well-being, social function, sexual function, satisfaction with sexual function, physical health composite and mental health composite scores of MSQOL-54. MSPSS total score was positively correlated with emotional well-being score of MSQOL-54. Conclusions: In MS patients, there is a high prevalence of psychopathology and it is associated with quality of life, perceived social support and psychosocial adjustment of the patients. Quality of life is reduced especially in emotional and mental aspects in patients with a psychiatric diagnosis. Diagnosis and treatment of psychopathology in MS patients seems crucial to decrease disease burden.